Multicenter Analysis of Immune Biomarkers and Heart Transplant Outcomes: Results of the Clinical Trials in Organ Transplantation‐05 Study. Issue 1 (10th August 2015) - Starling, R. C.; Stehlik, J.; Baran, D. A.; Armstrong, B.; Stone, J. R.; Ikle, D.; Morrison, Y.; Bridges, N. D.; Putheti, P.; Strom, T. B.; Bhasin, M.; Guleria, I.; et al.
Abstract : Identification of biomarkers that assess posttransplant risk is needed to improve long‐term outcomes following heart transplantation. The Clinical Trials in Organ Transplantation (CTOT)‐05 protocol was an observational, multicenter, cohort study of 200 heart transplant recipients followed for the first posttransplant year. The primary endpoint was a composite of death, graft loss/retransplantation, biopsy‐proven acute rejection (BPAR), and cardiac allograft vasculopathy (CAV) as defined by intravascular ultrasound (IVUS). We serially measured anti‐HLA‐ and auto‐antibodies, angiogenic proteins, peripheral blood allo‐reactivity, and peripheral blood gene expression patterns. We correlated assay results and clinical characteristics with the composite endpoint and its components. The composite endpoint was associated with older donor allografts (p < 0.03) and with recipient anti‐HLA antibody (p < 0.04). Recipient CMV‐negativity (regardless of donor status) was associated with BPAR (p < 0.001), and increases in plasma vascular endothelial growth factor‐C (OR 20; 95%CI:1.9–218) combined with decreases in endothelin‐1 (OR 0.14; 95%CI:0.02–0.97) associated with CAV. The remaining biomarkers showed no relationships with the study endpoints. While suboptimal endpoint definitions and lower than anticipated event rates were identified as potential study limitations, the results of this multicenter study do not yet support routine use of the selected assays as noninvasive approaches to detect BPAR and/or CAV following heart transplantation. Abstract : In this observational, multicenter, cohort study of 200 heart transplant recipients, the investigators find that acute rejection and evidence of vasculopathy at 1 year posttransplant correlates with several epidemiological parameters, anti‐HLA antibodies and plasma angiogenesis‐related factors, but not with a panel of cellular and molecular biomarkers. See also Van Aelst et al onpage 99 .